Rafael Moneo selected works - Fernández-Galiano, Luis 1950- (AV monografías, 2022)
"With a prolific career spanning more than five decades, Rafael Moneo is considered a key figure in contemporary Spanish architecture, and his work has inspired several generations of architects around the world. [This publication] gathers forty of his most prominent buildings in a chronological itinerary, from 1970 to our days. The monograph shows the variety and complexity of his extensive built oeuvre, and reveals some common features of all his projects, such as the prominence of light, the use of traditional materials and techniques, and the effort to respond to the specific context, both natural and urban as well as historic and cultural"--publisher's description